Pathomorphological features of the pancreas depending on chronic pancreatitis duration - Mikheiev, I.; Skrypko, V.; Pasko, A.; Popadynets, O.; Міхеєв, Юрій Олександрович (My University, 2024)
The purpose of the study was to assess the morphological and immunohistochemical characteristics of the pancreatic parenchyma depending on СР duration. Methods: A total of 147 (57.1%) patients were examined retrospectively. A prospective comparative study involving 257 patients analyzed the short and long-term outcomes to evaluate the effectiveness of the “early surgery” strategy developed at the clinic and the surgical management methods for СР. The study conducted a morphological and immunohistochemical assessment of the pancreatic parenchyma, analyzing the long-term outcomes of the primary pathogenetic surgical treatments for СР. Results: Morpho-functional changes in the pancreatic parenchyma, observed more than three years (median 5.85 years) after the onset of CP clinical manifestations, were characterized by progressive fibrosis due to increased expression of type I collagen and fibronectin, which resulted in dense cuff-like perineural and perivascular fibrosis and stenosis of the pancreatic ducts around tubular complexes, clinically corresponding to the presence of intense pain syndrome.
Keywords: pancreas; chronic pancreatitis; morphological changes; fibrosis